Self-assembly and energy transfer in artificial light-harvesting complexes of bacteriochlorophyll c with astaxanthin - Alster, J; Polívka, T; Arellano, J B; Hříbek, P; Vácha, F; Hála, J; Pšenčík, J (Photosynthesis research, 2012)
Chlorosomes, the light-harvesting antennae of green photosynthetic bacteria, are based on large aggregates of bacteriochlorophyll molecules. Aggregates with similar properties to those in chlorosomes can also be prepared in vitro. Several agents were shown to induce aggregation of bacteriochlorophyll c in aqueous environments, including certain lipids, carotenes, and quinones. A key distinguishing feature of bacteriochlorophyll c aggregates, both in vitro and in chlorosomes, is a large (>60 nm) red shift of their Q(y) absorption band compared with that of the monomers. In this study, we investigate the self-assembly of bacteriochlorophyll c with the xanthophyll astaxanthin, which leads to the formation of a new type of complexes. Our results indicate that, due to its specific structure, astaxanthin molecules competes with bacteriochlorophylls for the bonds involved in the aggregation, thus preventing the formation of any significant red shift compared with pure bacteriochlorophyll c in aqueous buffer. A strong interaction between both the types of pigments in the developed assemblies, is manifested by a rather efficient (~40%) excitation energy transfer from astaxanthin to bacteriochlorophyll c, as revealed by fluorescence excitation spectroscopy. Results of transient absorption spectroscopy show that the energy transfer is very fast (<500 fs) and proceeds through the S(2) state of astaxanthin.
Keywords: Energy Transfer; Light; xanthofyly; světlosběrné proteinové komplexy; spektrální analýza; Spectrum Analysis; Chlorobium; bakteriochlorofyly; Light-Harvesting Protein Complexes; Xanthophylls; Bacteriochlorophylls; fotosyntéza; přenos energie; Photosynthesis; Bacterial Proteins; světlo; bakteriální proteiny